Effect of COVID-19 pandemic on eating habits and lifestyle of college students in Tabriz, Iran: a cross-sectional study - Maryam Rafraf; Roghayeh Molani-Gol; Mina Sahebjam (Frontiers Media S.A., 2023)
BackgroundThe pandemic of coronavirus disease (COVID-19) has influenced lifestyle behaviors and the health of populations worldwide. The purpose of this study was to determine the effects of the COVID-19 pandemic on the eating habits and lifestyle behaviors of Tabriz University of Medical Sciences students in Tabriz, Iran.MethodsThis cross-sectional study was conducted on 220 college students selected using a convenience sampling method in May-June 2022. Data were collected by the questionnaire, which included information on eating habits, physical activity, smoking, watching television, social media use, sleep, anxiety and stress, and smoking before and during the pandemic. The Chi-square test was used to analyze the association of COVID-19 with lifestyle behaviors.ResultsThe median age of participants was 22.00 (IQR: 3.00) years old. The median BMI was 21.69 (IQR: 3.82) kg/m2, and 74.5% of participants had a BMI of 18.5 to 25 kg/m2. Around 34.5% of participants reported a weight gain during the pandemic. During the pandemic, students' eating habits improved by maintaining a regular meal pattern, eating a balanced diet, consuming 2-3 servings of milk or its products, consuming one or more servings of pulses, eggs, or meat per day, decreasing consumption of fast food, fried, and junk foods, adding less sugar to meals and beverages, and consuming fewer sugar-sweetened beverages and foods with high sugar (all p = 0.000). They also reported less physical activity and more sitting and screen time. Sleep time and poorer quality of sleep increased during the pandemic (p = 0.000). Feeling stress or anxiety in a day increased, and 2.2% of our participants decided to smoke. The biggest reasons for eating habits changes were less eating out, fear of coronavirus spreading through food, preferring home-cooked food, and improved knowledge about nutrition.ConclusionThe results indicated that the eating habits of university students improved; however, participants stated increased weight gain, screen, sitting, and sleep time, declined physical activity, worse sleep quality, and feeling stress or anxiety during the COVID-19 pandemic. The findings can help to develop nutritional and behavioral recommendations for maintaining adults' health during and after the pandemic.